Leadership Behaviour Association with Human Resource Management Practice in Selected Ethiopian Sport Federations - Aschenaki Taddese; Tesfay Asgedom; Samson Tadesse (Atatürk University, 2024)
Leadership behavior and human resource management practices (HRMP) in sport organizations is crucial for organizational success. Effective leadership behavior can positively influence human resource management practices, while these practices can also impact leadership behavior. By understanding and leveraging this relationship, sport organizations can create a positive work environment, enhance employee performance, and achieve their organizational goals. To objective of the study was to find the association between Leadership Behaviour and HRMP of selected Ethiopian Sport Federations. In this study, the sequential explanatory research design was used. a sample size of 95 respondents (n = 95) from Ethiopian Football Federation and Ethiopian Athletics Federation was selected using stratified sampling technique. The variable of the study was leadership behaviour and HRMP. In addition to this, standardized questionnaires, document analysis, focus group discussions and semi-structured interviews were used to collect the data. Quantitative data was analysed using Spearman correlation coefficient while qualitative data were transcribed and interpreted. The result of the study shows that there was significant association between leadership behaviour and HRMP, r = 0.41, p = .001. The study concluded that Ethiopian selected federation leadership behavior has contribution for effectiveness HRMP. However, utilizing modern technology, robust monitoring and evaluation mechanism, adequate guidelines, standards and manuals, employee knowledge, skills and attitudes, physical facilities, financial capacities and satisfaction athletes, coaches, officials and stakeholders were not up to the required level.